Effect of poly (lactide‐co‐glycolide) (PLGA)‐coated beta‐tricalcium phosphate on the healing of rat calvarial bone defects: a comparative study with pure‐phase beta‐tricalcium phosphate. Issue 11 (8th January 2016) - Bizenjima, Takahiro; Takeuchi, Takahiro; Seshima, Fumi; Saito, Atsushi
Abstract: Objectives: To investigate the effect of poly (lactide‐co‐glycolide) (PLGA)‐coated β‐tricalcium phosphate (TCP) as a scaffold on bone regeneration in rat calvaria. Material and Methods: Bilateral critical‐sized defects were created in the calvaria of 20 Sprague Dawley rats. Defects of each rat were filled with pure‐phase β‐TCP or PLGA/β‐TCP, or left as unfilled control. The healing was evaluated by micro‐computed tomography, histological, and immunohistochemical analyses. Tartrate‐resistant acid phosphatase (TRAP) staining was also performed to assess the resorption activity. Results: At 4 weeks, ingrowth of cells from the surrounding tissue into the β‐TCP and PLGA/β‐TCP biomaterials were observed in the defect area, and new bone formation had started. At 6 weeks, the value for defect closure in the β‐TCP group was significantly greater than that in the unfilled control ( P  <   0.01). A significantly greater level of new bone formation was found in the β‐TCP group ( P  <   0.01) and PLGA/β‐TCP group ( P  <   0.05) than that in the control group, while no significant difference was found between the β‐TCP and PLGA/β‐TCP groups. At both time points, the height of new tissue/biomaterial in the central third of the defect was significantly increased when the β‐TCP or PLGA/β‐TCP was used. Proliferating cell nuclear antigen ‐positive cells were observed around and inside the β‐TCP or PLGA/β‐TCP, and TRAP‐positive cells were found at the surface of the biomaterials, suggesting that remodeling was occurring. Conclusion: The application of PLGA‐coated β‐TCP could promote bone regeneration to similar extent as the β‐TCP biomaterial in this in vivo model.